2016
DOI: 10.1161/jaha.116.003815
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Intake From Diet and Supplements and the Risk of Coronary Artery Calcification and its Progression Among Older Adults: 10‐Year Follow‐up of the Multi‐Ethnic Study of Atherosclerosis (MESA)

Abstract: BackgroundRecent randomized data suggest that calcium supplements may be associated with increased risk of cardiovascular disease (CVD) events. Using a longitudinal cohort study, we assessed the association between calcium intake, from both foods and supplements, and atherosclerosis, as measured by coronary artery calcification (CAC).Methods and ResultsWe studied 5448 adults free of clinically diagnosed CVD (52% female; aged 45–84 years) from the Multi‐Ethnic Study of Atherosclerosis. Baseline total calcium in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
109
1
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 155 publications
(118 citation statements)
references
References 53 publications
1
109
1
7
Order By: Relevance
“…47,48 Furthermore, several studies demonstrated that routine vitamin and mineral supplementation in certain populations, for instance in elderly patients, could lead to a worse outcome. [49][50][51] Our finding supports the hypothesis that the net effect of MVM supplementation in the general population for CVD prevention is neutral.…”
Section: Discussionsupporting
confidence: 84%
“…47,48 Furthermore, several studies demonstrated that routine vitamin and mineral supplementation in certain populations, for instance in elderly patients, could lead to a worse outcome. [49][50][51] Our finding supports the hypothesis that the net effect of MVM supplementation in the general population for CVD prevention is neutral.…”
Section: Discussionsupporting
confidence: 84%
“…Importantly, because the mean age at the beginning of follow-up for these women was 51.5 y, the relation of vitamin D and calcium intakes and risk of early menopause (,45 y old) remains unclear. In addition, this study did not distinguish calcium and vitamin D from dietary compared with supplemental sources, which has proven to be an important distinction in previous studies of reproductive-related conditions and other outcomes (18,24,25).…”
Section: Introductionmentioning
confidence: 88%
“…However, concerns have been raised owing to associations between calcium supplements and an increased risk of vascular calcification and cardiovascular events (3, 15, 71). Phosphorus balance has not been studied as rigorously as calcium balance, although older metabolic studies suggest that high intakes of inorganic phosphorus additives could lead to positive phosphorus balance (46, 153).…”
Section: Phosphorus Balance Studies In Humansmentioning
confidence: 99%